The Justice in Mercy - Couenhoven, Jesse (Journal of religious ethics, 2020)
It is natural to wonder how mercy is related to justice. I focus in this essay on a more limited question: how should we relate mercy and retributive justice? My suggestion is that attending to our situation as moral agents can help us solve this conundrum. I offer a pessimistic reading of our situation. Because of original sin and related forms of bad moral luck, we have limited control over our attitudes and actions. This has a surprisingly hopeful upshot, since our unfortunate condition makes it appropriate to respond to one another mercifully. I suggest that this response can take two forms. Without collapsing justice into mercy, it is right to make our approach to justice and punishment more merciful and to recognize the fittingness of “erring” on the side of mercy when we are uncertain how to apportion blame.